Analysis of The Influence of Digital Marketing Strategy on Repurchase Intention with Competitive Advantage and Perceived Brand Interactivity as Mediating Variables at OKI-I Okonomiyaki Shop, Malang City - Rizky Dwi Novrianto (Green Publisher Indonesia, 2024)
This research analyzed the influence of Digital Marketing Strategy on Repurchase Intention with Competitive Advantage and Perceived Brand Interactivity as moderating variables at Kedai Oki-I Okonomiyaki, Malang City. The research method used a descriptive explanatory approach with multiple linear regression analysis, path analysis, and hypothesis testing techniques. The research population was 700 visitors with a sample of 255 respondents taken by proportional random sampling. Data were collected through questionnaires and processed using SPSS version 25. The results showed that Digital Marketing Strategy had a significant positive effect on Repurchase Intention, Competitive Advantage, and Perceived Brand Interactivity. Competitive Advantage and Perceived Brand Interactivity also had a significant positive effect on Repurchase Intention and moderated the influence of Digital Marketing Strategy on Repurchase Intention.